Analisis gaya belajar siswa kelas 5 SD N Sambirejo terhadap daya serap matematika materi KPK dan FPB - Agata, Della; Prihastari, Ema Butsi; Rahman, Ifa Hanifa (Universitas Sebelas Maret, 2024)
This research is intended to understand the analysis of students' learning styles towards understanding mathematics learning. This research was motivated by students' difficulties in solving mathematics problems, especially in KPK and FPB material. This difficulty is experienced by students when determining the correct KPK and FPB calculation operations, as well as difficulties in operating factor trees. The method used is qualitative with a qualitative descriptive approach. Data collection techniques include observation, questionnaires, interviews and documentation. Based on the research results, grade 5 students at SD N Sambirejo for the 2023/2024 academic year show a variety of learning styles, but the learning style generally applied by teachers is more dominant in the auditory aspect. This trend has an impact on the absorption capacity of diverse students. Students with a visual learning style have good learning absorption, students with an auditory learning style have superior absorption and students with a kinesthetic learning style have mixed and unstable absorption.